Studies on Zero Energy Cool Chamber for Storage of Ber (Zizyphus mauritiana Lamk.) Fruits under Semi-arid Conditions - Dhaka, R S; Lal, G; Fageria, M S; Agrawal, M (Annals of Arid Zone, 2016)
Ber fruits harvested at color-turning stage were stored under two storage conditions, i.e., in cool chamber and at ambient condition. Four year study revealed that storage in sealed polythene bags in cool chamber reduced PLWand spoilage percentage and recorded better. quality attributes.